Establishment and characterization of an immortalized epithelial cell line from human gallbladder - Wang, Ziyi; Wang, Shijia; Jia, Ziheng; Zhao, Yuhao; Yang, Mao; Yan, Weikang; Chen, Tao; Xiang, Dongxi; Shao, Rong; Liu, Yingbin (Frontiers in Oncology, 2022)
Background Although a plethora of studies have employed multiple gallbladder cancer (GBC) cell lines, it is surprisingly noted that there is still lack of a normal gallbladder epithelial cell line as a normal counterpart, thus impeding substantially the progress of mechanistic studies on the transformation of normal epithelial cells to cancer. Here, we created a normal gallbladder epithelial cell line named L-2F7 from human gallbladder tissue. Methods Gallbladder tissues from a diagnosed cholecystitis female patient were collected, and epithelial cells were enriched by magnetic cell sorting. Then, the cells were immortalized by co-introduction of human telomerase reverse transcriptase (hTERT) and Simian virus 40 large T antigen (LT-SV40) via a lentivirus infection system. After clonal selection and isolation, L-2F7 cells were tested for epithelial markers CK7, CK19, CK20, and CD326, genomic feature, cell proliferation, and migration using Western blot, immunofluorescence, whole genome sequencing, karyotyping, and RNA sequencing. L-2F7 cells were also transplanted to Nude (nu/nu) mice to determine tumorigenicity. Results We successfully identified one single-cell clone named L-2F7 which highly expressed epithelial markers CD326, CK7, CK19, and CK20. This cell line proliferated with a doubling time of 23 h and the epithelial morphology sustained over 30 passages following immortalization. Transient gene transduction of L-2F7 cells led to expression of exogenous GFP and FLAG protein. L-2F7 cells exhibited both distinct non-synonymous mutations from those of gallbladder cancer tissues and differential non-cancerous gene expression patterns similar to normal tissue. Although they displayed unexpected mobility, L-2F7 cells still lacked the ability to develop tumors. Conclusion We developed a non-cancerous gallbladder epithelial cell line, offering a valuable system for the study of gallbladder cancer and other gallbladder-related disorders.